Using The Socratic Method In Teaching The Subject “Fundamentals Of State And Law” (The Peerian Journal, 2025)
This article examines the possibilities of using the Socratic method in teaching the subject “Fundamentals of State and Law.” The Socratic method helps develop students’ critical and logical thinking skills, enabling them to substantiate their views and deepen their knowledge through discussions. The article provides a detailed analysis of the essence of this method, its origin, stages of application, and advantages. Additionally, examples of effective use of the Socratic method in discussing legal issues are given.